2016
DOI: 10.1118/1.4953830
|View full text |Cite
|
Sign up to set email alerts
|

Heterodyne frequency‐domain multispectral diffuse optical tomography of breast cancer in the parallel‐plane transmission geometry

Abstract: Imaging with a novel parallel-plate DOT breast imager that employs highly parallel, high-resolution CCD detection in the frequency-domain was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 80 publications
0
17
0
1
Order By: Relevance
“…Compared to these imaging modalities, near infrared spectroscopy (NIRS) and spectral tomography (NIRST) provide potential advantages due to their noninvasive nature, relatively low cost and portable size [7][8][9]. Pilot studies have shown that NIRS and NIRST can assess the intrinsic biophysical composition of tissue, in terms of absorber concentrations of deoxy-hemoglobin (Hb) and oxy-hemoglobin (HbO), water and lipids [10][11][12], as well as the scattering signatures attributed to ultra-structural cellular density and size ensemble associated with the extracellular matrix and subcellular constituents in healthy breast tissues [13,14]. These can differentiate malignant from benign pathology [15,16], and have shown success in monitoring the tumor response to treatments [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to these imaging modalities, near infrared spectroscopy (NIRS) and spectral tomography (NIRST) provide potential advantages due to their noninvasive nature, relatively low cost and portable size [7][8][9]. Pilot studies have shown that NIRS and NIRST can assess the intrinsic biophysical composition of tissue, in terms of absorber concentrations of deoxy-hemoglobin (Hb) and oxy-hemoglobin (HbO), water and lipids [10][11][12], as well as the scattering signatures attributed to ultra-structural cellular density and size ensemble associated with the extracellular matrix and subcellular constituents in healthy breast tissues [13,14]. These can differentiate malignant from benign pathology [15,16], and have shown success in monitoring the tumor response to treatments [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Диффузионное приближение к уравнению переноса излучения (УПИ) довольно точно описывает баланс энергии в сильно рассеивающих средах, таких как био-логические ткани или их фантомы [3,8,16]. Плотность потока фотонов для множества моделируемых точек с координатами x, y, z может быть представлена как функция времени или как функция частоты [17]. Цели данной работы наиболее соответствует диффузионное приближение к УПИ для ультракоротких импульсов (функция времени) следующего вида [10]:…”
Section: моделирование миграции фотонов в сильно рассеивающих средах unclassified
“…The value of the transport index describes specific tissue cellular structure, while the value of the coefficient of absorption enables the evaluation of biological chromophore concentration (oxyhemoglobin, deoxyhemoglobin, water, fats, collagen, etc.) [48][49][50][51]. The total hemoglobin concentration reflects blood filling of the tissue, shows oxygen supply, deoxyhemoglobin reflects its consumption.…”
Section: Diffuse Optical Spectroscopymentioning
confidence: 99%